A zonal non-equilibrium approach to model temperature gradients during ventless bottom filling of pressurized cryotanks for natural gas-powered ships. (1st December 2019) - Thiaucourt, Jonas; Marty, Pierre; Hetet, Jean-François; Robert, Pascal; Delaire, Etienne
Abstract: Liquefied Natural Gas (LNG) as a fuel is seen as a solution to curb harmful emissions in shipping and its quick uptake is now significant. New LNG bunkering scenarios are hence rising with a growing range of technical challenges. In this paper, a thermodynamic zonal model is established to assess the temperature gradients induced by a ventless bottom filling. The reservoir is divided into three control volumes. A condensation model at the liquid/vapor interface is proposed. Thermophysical properties are interpolated in tables allowing calculations with a good precision and a CPU time reduced of 68% compared to equation of state software direct calls. The non-equilibrium phenomenon of condensation blocking is highlighted. Then, the impact of the loading pressure is further investigated. As a result, it is shown that bottom filling rate at high pressure (around 11 bars absolute) can compete with vented filling techniques only if the tank can deal with strong spatial (liquid/vapor) and temporal temperature gradients, respectively of order 94.3 K and 0.19 K/s. Highlights: Bottom no vent filling of LNG marine tanks generates condensation blocking effect. Condensation blocking effect impedes LNG bunkering. Condensation blocking effect produces strong thermal gradients.